Odpowiedź:
a)
(2x - 1)³ - 4x(2x - 1)(x + 2) > 0
8x³ + 12x² - 6x + 1 - (8x² - 4x)(x + 2) > 0
8x³ + 12x² - 6x + 1 - (8x³ + 16x² - 4x² - 8x) > 0
8x³ + 12x² - 6x + 1 - 8x³ - 16x² + 4x² + 8x > 0
2x +1 > 0
2x > - 1
x > - 0,5
x ∈ (-0,5; +∞)
b)
(x + 2)(x² - 2x + 4) - x(x - 3)² ≥ 3x(2x - 3) + 8
x³ + 8 -x(x² + 6x + 9) ≥ 6x² - 9x + 8
x³ + 8 - x³ - 6x² + 9x ≥ 6x² - 9x + 8
- 12x² + 18x ≥ 0
6x (-2x + 3) ≥ 0
6x ≥ 0 v -2x + 3 ≥ 0
x ≥ 0 v -2x ≥ -3
x ≥ 0 v [tex]x \leq \frac{2}{3}[/tex]
x ∈ < 0; [tex]\frac{2}{3}[/tex] >